Effect of Climate Change on Lyme Disease Risk in North America - Brownstein, John S. (2005)
An understanding of the influence of climate change on Ixodes scapularis, the main vector of Lyme disease in North America, is a fundamental component in assessing changes in the spatial distribution of human risk for the disease. We used a climate suitability model of I. scapularis to examine the potential effects of global climate change on future Lyme disease risk in North America. A climate-based logistic model was first used to explain the current distribution of I. scapularis in North America. Climate change scenarios were then applied to extrapolate the model in time and produce forecasts of vector establishment. The spatially modeled relationship between I. scapularis presence and large-scale environmental data generated the current pattern of I. scapularis across North America with an accuracy of 89% (p<0.0001). Extrapolation of the model revealed a significant expansion of I. scapularis north into Canada with an increase in suitable habitat of 213% by the 2080’s. Climate change will also result in a retraction of the vector from southern United States, and movement into the central United States. This report predicts the effect of climate change on Lyme disease risk and specifically forecasts the emergence of a tick-borne infectious disease in Canada. Our modeling approach could thus be used to outline where future control strategies and prevention efforts need to be applied.